2022
DOI: 10.3389/fmicb.2022.868347
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Povidone Iodine Against Microbial Biofilms in Breast Implants With Different Textures: Results From an in vitro Study

Abstract: BackgroundIn the practice of breast augmentation and reconstruction, implant irrigation with various solutions has been widely used to prevent infection and capsular contracture, but to date, there is no consensus on the optimal protocol to use. Recently, application of povidone iodine (PI) for 30 min has shown in vitro to be the most effective irrigating formula in reducing contamination in smooth breast implants. However, as 30 min is not feasible intraoperatively, it is necessary to determine whether shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…20,21 The implant's surface itself is also of significance in local contamination and ingrowth of bacteria. 12,22 The uneven surface of textured implants offers more possibilities for pathogens to settle and evade the immune system, despite meticulous antisepsis, therefore possibly resulting in an increase of unnoticed implant contamination and subclinical infection rates leading to implant damage. Similar effects have been documented in the pathogenesis of BIA-ALCL.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The implant's surface itself is also of significance in local contamination and ingrowth of bacteria. 12,22 The uneven surface of textured implants offers more possibilities for pathogens to settle and evade the immune system, despite meticulous antisepsis, therefore possibly resulting in an increase of unnoticed implant contamination and subclinical infection rates leading to implant damage. Similar effects have been documented in the pathogenesis of BIA-ALCL.…”
Section: Discussionmentioning
confidence: 99%
“…114 The pretreatment of smooth or textured breast implant surfaces with 10% PI for as little as 1 minute in vitro can prevent growth of S. epidermidis or S. aureus applied to the device surface but does not significantly affect bacterial load or living cells. 115…”
Section: Antibiotic Irrigation In Vitro Evidencementioning
confidence: 99%
“…In breast surgery with implants, infection of the surgical site as a consequence of bacterial colonization of the implant is one of the most relevant complications [ 87 ]. The presence of bacterial biofilm has been correlated with the development of capsular contracture, which is the most frequent complication in breast implant surgery reported in 5.2% to 30% of patients with breast implants [ 59 , 88 ].…”
Section: Biofilm and Device-related Infectionsmentioning
confidence: 99%
“…One of the most recent studies regarding preventive measures during breast surgery demonstrated that povidone–iodine used for implant irrigation was the best antiseptic capable of eradicating biofilm [ 87 , 90 ]. However, povidone–iodine absorption may be directly related to implant texture rather than to exposure time [ 87 ].…”
Section: Biofilm and Device-related Infectionsmentioning
confidence: 99%
See 1 more Smart Citation